The translation profession in Malaysia: the translator’s status and self-perception - Myoung , Sook Kang; Krishnavanie Shunmugam (Penerbit UKM, 2014)
This paper aims to discuss the current status of translators practising in Malaysia and their perceptions towards the profession. The study was motivated by the dearth of literature on the status of the translator’s profession in Malaysia. Past studies have shown that translation is not considered a full-fledged profession in many other countries. Translators also do not perceive their own job as belonging to a profession due to a number of reasons. This study which adopts hermeneutic phenomenology as its method of inquiry is mostly qualitative in nature with an inclusion of some basic quantitative measures. The findings of this study has revealed that though Malaysian translators regard themselves as professionals in society, clients and the public unfortunately do not share the same views. The translators also cited unfair competition from amateur translators and unprofessional practices in their profession due to a lack of code of ethics, as challenges which seriously undermine the status of their professions. The findings of this study markedly highlight the concerted effort that is needed to set up a professional body to represent the translators in Malaysia.